Digitalisasi layanan perpustakaan: optimalisasi peran pustakawan dalam mewujudkan academic smart library - Novitasari, Rizki Cahya; Ramli, Akhmad; Sudadi, Sudadi (Universitas Madako Tolitoli, 2025)
The digitalization of library services has driven significant changes in librarians' roles, enhancing the quality of information services in higher education environments. The purpose of this study is to determine how librarians can optimize library services in higher education institutions to realize an Academic Smart Library. Higher education libraries function as learning resource centers that help meet users' information needs, requiring human resources with competence, experience, and the ability to adapt to digital technology. Librarians are required to provide effective, high-quality information services that meet user standards and expectations. Digitalization efforts not only affect information management systems but also require librarians to develop digital competencies, information literacy, and service innovation to increase service effectiveness. This study used a literature review method, collecting secondary data from scientific publications, journals, and related academic documents. The data were analyzed using theories and previous research to conclude strategies for optimizing librarians' roles in developing digital libraries. The results of the study indicate that the successful implementation of an Academic Smart Library is influenced by the librarian's ability to lead digital transformation by improving competencies, managing information technology, and strengthening their role as knowledge facilitators for the academic community.